EFFECT OF DRILLING PARAMETERS ON THRUST FORCE AND TORQUE DURING DRILLING OF ALUMINIUM 6061 ALLOY - BASED ON TAGUCHI DESIGN OF EXPERIMENTS (Journal of Mechanical Engineering, 2017)
Hole generating process with drill bit called as drilling, which is very important because large portion of overall machining of any component in production industry needs assemble of parts to make a final shape with rivets and fasteners. It is well known that the drill point geometry has a significant effect on thrust force exerted by a drill bit while drilling. In this study, experimentally investigate the influence of drilling parameters such as pointangle, clearance angle, cutting speed, feed rate and drill diameter on the thrust force and torque in drilling. Drilling experiments have been conducted over a wide a range of machining conditions such as cutting speed varied in the range 500 rpm to 1000 rpm in 3steps, feed rate varied from 0.3 to 0.6mm /min in three steps using two flutesuncoated conventional twist drills of three different diameters (8, 10 and 12mm) with 1180 point and 450 helix angles. Drill bits tool geometry altered by tool&cutter grinder and obtained 1100, 1000 point angles also clearance angles varied by 40, 60 and 80. Holes are performed on Aluminium 6061 alloy material of rectangular cross section having dimensions 300mmx50mmx10mm as per taguchi technique. A kistler (type 9272), four components drill tool dynamometer was used to measure thrust force (Th) and torque (M) exerted by the drill bit during hole making on a work material further the signal was processed to a computer by a multichannel signal amplifier (Kistler 5070 type) was used to record the thrust force and torque. Finally, ANOVA test have been carried out to confirm thesignificance of factors considered during drilling and compare the predicted values with the experimental values on influence of factors on responses.